Sounds in Fawasil Verses and Its Relation to Meaning: Phonetic Studies of the Qur'an in Q.S al-Buruj - Rahma, Raisya Miftakhul (Aqwal: Journal of Qur'an and Hadis Studies, 2022)
This paper is entitled "The Sound of the Fawasil Verse and Its Relation to the Meaning: Phonetic Study of the Qur'an in Q.S al-Buruj", aims to examine the beauty of the sound produced from the Fawasil verse of Q.S al-Buruj and its relation to the meaning contained in the verse, because every letter in the Qur'an is a miracle that proves that the Qur'an is Kalamullah. This paper is a qualitative research with a library research approach and the paper uses phonetic theory. The subject of this paper is fawasilul ayat. Data will be collected using documentation analytical methods and data will be analyzed using descriptive percentage analysis methods. The conclusion of this paper is that the fawasil verse is evidence of the fluency of the Qur'an which explains that the Qur'an did not come from human speech. The beauty of the fawasil verse of Q.S al-Buruj lies in the last letter that forms the rhyme and the last syllable that produces a long sound. In addition, the sounds of the letters in the fawasil verse are related to their meaning content. The difference is very visible when the Qur'an explains two contradictory things, namely about the recompense for the disbelievers and the recompense for the believers which is voiced with a sound of inhibition and silent vibration.